Exploring Natural Alkaloids Berberine for Sustainable Corrosion Control: A Case Study on Mahonia nepalensis Extracts - Das, Anju Kumari; Koju, Gayatri Maiya; Das, Maya; Karki , Nabin; Gupta, Dipak Kumar; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2026)
This study examines the corrosion inhibition potential of the dichloromethane/methanol (9:1) fraction derived from Mahonia nepalensis extract in a corrosive medium. Remarkably, this fraction, containing only 0.192 ppm of berberine, a prominent isoquinoline alkaloid known for its biological activity, exhibited a high corrosion inhibition efficiency of 86.23%. This significant performance at such a low concentration suggests that berberine, even in trace amounts, plays a vital role in passivating the metal surface, possibly through adsorption mechanisms and the development of a protective film. The results highlight the ability of Mahonia nepalensis as a potential alternative source of environmentally benign corrosion inhibitors and emphasize the potency of plant-derived bioactive compounds in corrosion control. These findings also open avenues for further exploration of berberine and related phytochemicals for sustainable industrial applications.